New Blood Pressure–Associated Loci Identified in Meta-Analyses of 475 000 Individuals. (October 2017) - Kraja, Aldi T.; Cook, James P.; Warren, Helen R.; Surendran, Praveen; Liu, Chunyu; Evangelou, Evangelos; Manning, Alisa K.; Grarup, Niels; Drenos, Fotios; Sim, Xueling; Smith, Albert Vernon; Amin, Najaf; et al.
Abstract : Background—: Genome-wide association studies have recently identified >400 loci that harbor DNA sequence variants that influence blood pressure (BP). Our earlier studies identified and validated 56 single nucleotide variants (SNVs) associated with BP from meta-analyses of exome chip genotype data. An additional 100 variants yielded suggestive evidence of association. Methods and Results—: Here, we augment the sample with 140 886 European individuals from the UK Biobank, in whom 77 of the 100 suggestive SNVs were available for association analysis with systolic BP or diastolic BP or pulse pressure. We performed 2 meta-analyses, one in individuals of European, South Asian, African, and Hispanic descent (pan-ancestry, ≈475 000), and the other in the subset of individuals of European descent (≈423 000). Twenty-one SNVs were genome-wide significant ( P <5×10 −8 ) for BP, of which 4 are new BP loci: rs9678851 (missense, SLC4A1AP ), rs7437940 ( AFAP1 ), rs13303 (missense, STAB1 ), and rs1055144 ( 7p15.2 ). In addition, we identified a potentially independent novel BP-associated SNV, rs3416322 (missense, SYNPO2L ) at a known locus, uncorrelated with the previously reported SNVs. Two SNVs are associated with expression levels of nearby genes, and SNVs at 3 loci are associated with other traits. One SNV with a minor allele frequency <0.01, (rs3025380 at DBH ) was genome-wide significant. Conclusions—: We report 4 novel loci associated with BP regulation, and 1 independent variant at an established BP locus. This analysis highlights several candidate genes with variation that alter protein function or gene expression for potential follow-up. Abstract : Supplemental Digital Content is available in the text.